Phases, Reflexives, and Definiteness. (7th July 2015) - Despić, Miloje
Abstract This paper investigates a puzzling correlation between two seemingly disparate phenomena: the crosslinguistic distribution of reflexive possessives and definiteness marking. As observed in Reuland 2007, 2011 and supported here by additional crosslinguistic evidence, reflexive possessives are available only in languages that either lack definiteness marking or encode definiteness postnominally. Languages that have prenominal (article‐like) definiteness marking, on the other hand, systematically lack reflexive possessives. I argue that such facts support a particular approach to reflexive binding—specifically, one that has the following properties: (i) binding domains are stated in terms of phases, (ii) in addition to CPs and vPs, DPs are phases, and (iii) DP is not universal. I closely examine another robust crosslinguistic correlation regarding definiteness marking—Bošković's (2008) Left Branch Extraction generalization—and show how it directly follows from the key assumptions of the analysis. I situate my proposals within a broader context of the phase theory, arguing that the syntactic representation of (in)definiteness is the crucial factor in determining the phasehood status of nominal categories. I extend my analysis to the clausal domain and discuss it in the context of languages that allow reflexives in the subject position.